Answer :


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 3√7 ;b = 4 ;c = -√7


= 3√7.-√7 = 3.-7 = -21


(using 7 = √7.√7)


And either of their sum or difference = b


= 4


Thus the two terms are 7 and - 3


Difference = 7 - 3 = 4


Product = 7× - 3 = - 21




( using 7 = √7.√7)



(√7 x-1)(3x + √7) = 0


(√7 x-1) = 0 or (3x + √7) = 0


x = 1/√7 or x = (-7)/√3


Roots of equation are


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics